The influence of exon 7 Phe389Leu polymorphism on P120 catenin interactions with e-cadherin and three-dimensional model rebuilt - Hu, J; Fei, Y; Liu, X S; Wang, F; Ma, D W; Liu, S L (Cellular and Molecular Biology, 2009)
The significance of endothelial P120 catenin (P120ctn) activity has been recognized for many years, however it was only recently that the complicated regulation of this constitutively expressed enzyme in endothelial cells was identified. A critical component of the P120ctn regulatory cycle in endothelial cells is its intracellular localization to caveolae. The caveolar coordination of P120ctn, more specifically its interaction with E-cadherin plays a major role in normal endothelial P120ctn activity and vascular bioavailability of nitric oxide. We have recently shown that the presence of P120ctn exon 7 Phe389Leu polymorphism caused diminished shear which was dependent catenin activation, was less extensively associated with caveolae, and had a decreased degree of interaction with E-cadherin. Here, we carried out preliminary investigations to identify possible mechanisms of the genotype-dependent endothelial cell responses we observed in our previous investigations. Through this approach we tested the hypothesis that computer simulations could provide insights regarding the contribution of this single nucleotide polymorphism to regulation of the P120ctn isoform. We observed that in the Phe/Leu and Leu/Leu mutant genotypes, the amount of P120ctn associated with E-cadherin was significantly lower. Additionally, we have shown, using a theoretical computational model, that mutation of an amino acid at position 389 might affect the protein-protein interactions and localization of the P120ctn protein. These alterations might also affect the protein function and explain the enhanced disease risk associated with the presence of Phe389Leu polymorphism in the P120ctn protein.